2021
DOI: 10.1029/2021gl096437
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Enhancement of Radiative Absorption by Black Carbon in Response to Particle Mixing Structure

Abstract: Global models estimate the effects of BC absorption based on its mass concentration, size distribution, particle morphology, and mixing structures of BC particles (Ramanathan & Carmichael, 2008;Riemer et al., 2019). Experimental evidence showed that the absorption enhancement, induced by mixing of BC with other nonabsorbing secondary aerosols, can be less than 1.05 (Cappa et al., 2012;Healy et al., 2015) or as large as 2. 4 (Peng et al., 2016). Furthermore, absorption enhancement obtained using the core-shell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 61 publications
(112 reference statements)
0
30
0
Order By: Relevance
“…It should be noted that the method has been well used in Wang, Li, et al. (2021) through the volume proportion of BC embedded in coating. Based on the TEM/EDS, we simply classified the soot particles into three types: Bare‐like, partly coated, and embedded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the method has been well used in Wang, Li, et al. (2021) through the volume proportion of BC embedded in coating. Based on the TEM/EDS, we simply classified the soot particles into three types: Bare‐like, partly coated, and embedded.…”
Section: Resultsmentioning
confidence: 99%
“…The 3D soot numerical models are generated from a tunable algorithm (Filippov et al., 2000) and one EMBS developed by Wang, Li, et al. (2021) based on the D f of soot particles and the numbers and sizes of monomers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method in identifying the fraction of the BC population with different degrees of sphericity is however independent of wavelengths, which can be applied to estimate E abs at other wavelengths. A recent study 35 found that E abs was nonlinearly related to the amounts of coatings but was importantly determined by the extent to which the BC was embedded in coatings. This may be essentially related to the particle shape distribution measured here, as embedded BC particles by coatings tend to be more spherical.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The scanning/transmission electron microscope (SEM/TEM) can also be used to determine the aerosol size and mixing states. Although it is difficult to analyze the particle continuously, it is an ideal technique to obtain the detailed mixing structure of aerosol species for individual particles. …”
Section: Introductionmentioning
confidence: 99%